2021
DOI: 10.3389/fimmu.2021.681110
|View full text |Cite
|
Sign up to set email alerts
|

ILC-You in the Thymus: A Fresh Look at Innate Lymphoid Cell Development

Abstract: The discovery of innate lymphoid cells (ILCs) has revolutionized our understanding of innate immunity and immune cell interactions at epithelial barrier sites. Their presence and maintenance are critical for modulating immune homeostasis, responding to injury or infection, and repairing damaged tissues. To date, ILCs have been defined by a set of transcription factors, surface antigens and cytokines, and their functions resemble those of three major classes of helper T cell subsets, Th1, Th2 and Th17. Despite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 101 publications
5
42
0
Order By: Relevance
“…These TLSCs can produce all known lymphoid lineages, including T cells, NK cells, B cells, and DCs (10, 34-37, 127, 128). In the bone marrow, the proliferation and fate HSCs are regulated by the stem cell factor (SCF) and its c-kit receptor in cooperation with Notch ligands and morphogenic factors, such as Wnt, Hedgehog, TGFb, and BMP (34,37,(127)(128)(129)(130). They regulate the stem cell self-renewal and differentiation into multiple lineages (35,127).…”
Section: Thymic Lymphoid Stem Cells and T Cell Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…These TLSCs can produce all known lymphoid lineages, including T cells, NK cells, B cells, and DCs (10, 34-37, 127, 128). In the bone marrow, the proliferation and fate HSCs are regulated by the stem cell factor (SCF) and its c-kit receptor in cooperation with Notch ligands and morphogenic factors, such as Wnt, Hedgehog, TGFb, and BMP (34,37,(127)(128)(129)(130). They regulate the stem cell self-renewal and differentiation into multiple lineages (35,127).…”
Section: Thymic Lymphoid Stem Cells and T Cell Developmentmentioning
confidence: 99%
“…Innate lymphoid cells (ILCs) are tissue-resident cells. They comprise NK cells and lymphoid tissue inducer (LTi) cells triggered through receptors for pathogens or inflammatory cytokines but not through the BCR or TCR antigen-specific receptors (128,(134)(135)(136). They are usually located at the mucosal barrier sites, and they regulate homeostasis and tissue repair in non-barrier organs (128,137,138).…”
Section: Thymic Innate Lymphoid Cellsmentioning
confidence: 99%
“…PBMCs are mixtures of multiple immune cells, which can be roughly divided into two immune cell subtypes, including innate immune cells (natural killer [NK] cells and monocytes) and adaptive immune cells (e.g., B cells and T cells). Furthermore, the discovery of innate lymphoid cells (ILCs) is critical for maintaining immune homeostasis or in response to inflammation [ 1 ]. T cells can be classified into CD4 + T (T helper cells) and CD8 + T (cytotoxic T cells), which can activate other immune cells and fight pathogens, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies have shown that ILCs are a branch of neonatal T-cell progenitors that colonize peripheral tissues in the third trimester (8,9). The CD4 − CD8 − double-negative (DN) T cells may differentiate into ILCs at DN1/ETP and DN2-DN3 transition stage, and this change is influenced by the intensity of Notch signaling and by E-ID protein and Bcl11b activity (10). In addition, Shin et al reported in particular that the differentiation of tissue-resident ILC2s may be because of DN2 ineffectively rearranging their g/d loci (10).…”
Section: Ilc2 Differentiation and Migrationmentioning
confidence: 99%
“…The CD4 − CD8 − double-negative (DN) T cells may differentiate into ILCs at DN1/ETP and DN2-DN3 transition stage, and this change is influenced by the intensity of Notch signaling and by E-ID protein and Bcl11b activity (10). In addition, Shin et al reported in particular that the differentiation of tissue-resident ILC2s may be because of DN2 ineffectively rearranging their g/d loci (10). The exact source of ILC2s that colonize in peripheral tissues and organs remains unknown.…”
Section: Ilc2 Differentiation and Migrationmentioning
confidence: 99%